Efektivitas Model Pembelajaran Project-Based Learning (PjBL) dengan Pendekatan Deep Learning dan STEAM Berbasis Etnomatematika dalam Meningkatkan Kemampuan Berpikir Reflektif pada Materi Pecahan Siswa Sekolah Dasar - Oktaviani Putri, Della; Rosmiati; Ladyawati, Erlin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model integrated with Deep Learning and STEAM approaches based on ethnomathematics in improving fifth-grade students’ reflective thinking skills on fraction material at SDN Kebraon 1 Surabaya. This research used a descriptive quantitative approach with pretest–posttest and student response questionnaires. The results showed a significant improvement in reflective thinking skills, indicated by moderate to high N-Gain scores. Students also gave positive responses, showing increased activeness, motivation, and better understanding of fraction concepts. Thus, this integrated approach is effective in creating meaningful and contextual learning.